Examining Tori Kelly's vocal improvisation on the song "Don't You Worry ‘Bout a Thing" - Bayu Pratama (Interlude: Indonesian Journal of Music Research, Development, and Technology, 2024)
This study examines the vocal improvisation in the performance of "Don't You Worry ‘Bout a Thing" from the movie Sing to improve the general comprehension of vocal methods in popular jazz music. This study aims to fill the vacuum in the current literature on vocal improvisation by studying the song's repertoire, with a particular focus on the vocal components. Researchers utilize a descriptive qualitative approach to observe and analyze the music directly, supplemented by intense listening sessions, to reveal the subtleties of vocal delivery. The goal is to explore the complex vocal improvisations that define the song, emphasizing how these aspects contribute to its overall artistic expression. This study not only provides instructional value for budding musicians but also enhances the general audience's understanding and enjoyment of jazz improvisation. This research offers a helpful update to existing knowledge by providing extensive insights into the vocal improvisation techniques used in "Don't You Worry ‘Bout A Thing". It addresses the need for more thorough data in this area. The findings emphasize the significance of improvisation in jazz, demonstrating how impromptu voice alterations can augment a song's emotional profundity and dynamic scope. The primary objective of this study is to enhance the comprehension and admiration of vocal improvisation among a broader range of people, promoting a more thorough involvement with jazz music and stimulating the growth of personal musical abilities and expressions.